THE ANALYSIS OF THE VIEWPOINT SHAPED BY THE INCLUSION OF NORMALLY DEVELOPING CHILDREN WITH TRAINABLE MENTALLY DISABLED CHILDREN BY THE WAY OF RECREATIONAL ACTIVITIES - PATLAR, Melike; BAYAZIT, Betül; UÇAR, Selami; DOLU, Umut; TUNCİL, Okan Serhat (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2018)
The purpose of this study is to examine the viewpoint that occurs as a result of the fusion of children with normal development and children with mentally retarded education through recreational activities. Confirmation of the study group to work within the schools of Kocaeli province which accepts to be carried out in the institution of work and regularly goes to the rehabilitation centers and the 12 rehabilitated mental disabilities randomly selected with IQ levels between 45-75, a total of 24 children, including 12 children with healthy and normal IQ levels, which were similar in terms of age characteristics selected randomly from the school giving birth. Details of the general and special nature, content, purpose, method, place, time and duration of working with children's families have been given to children with educable mental retardation and normal development. A total of 8 weeks of recreational activities were conducted for the study group, 2 days a week, 90 minutes a day. A 12- question questionnaire was prepared before and after the work schedule and prepared in such a way that children can be answered by the children created by the researchers. The distributions of the frequency and percentage values of the obtained data were evaluated in the SPSS 21.0 package program. As a result, it is found that children who have normal development after the pre-test do not have enough knowledge about disabled children and that they do not have any common activity before. In the final test after the implementation, normal development of children with mental retardation has been improved both in terms of behavior and outlook.